Duty of Care in Psychiatric Harm in Singapore - GOH, Yihan (Institutional Knowledge at Singapore Management University, 2008)
As with classics in the contemporary mass-market theatrical scene, legal classics appear to come in trilogies as well. Nowhere is this more aptly demonstrated than in tort law, where the three most important cases defining the test for duty of care in negligence are Donoghue v Stevenson [I932] A.C. 563, Anns v Merton LBC [I978] A.C. 728 and Caparo Industries Plc v,Dickrnan [I990] 2 A.C. 605. However, to suggest that the difficulties in negligence law have been clarified by these cases would be inaccurate. Indeed, not only is the actual test for duty of care unclear in England (see, e.g. Customs and Excise Commissioners v Barclays Bank Plc [2007] 1 A.C. 181), the test for duty of care in psychiatric harm cases is even more unsatisfactory. The Singapore Court of Appeal has recently attempted to resolve these difficulties. It first held in Spandeck Engineering (S) Pte Ltd v Defence Science & Technology Agency [2007] 4 S.L.R. 100 that the generally applicable test for duty of care in Singapore is essentially the two-stage Anns test (of proximity and policy considerations) irrespective of the type of damage claimed. It has now in Ngiam Kong Seng v Lim Chiew Hock [2008] SGCA 23 extended the Anns test to duty of care in psychiatric harm cases, while rejecting the English position in Page v Smith [I996] 1 A.C. 155.